The Effectiveness of the Principal's Managerial Leadership Role and Organizational Work Culture on Teacher Performance. - Riyanti Susiloningtyas; Fathur Rokhman; Eko Handoyo; Arif Yulianto; Amir Mahmud (International Conference on Science, Education, and Technology, 2023)
The purpose of this study is to describe and analyze the effect of the effectiveness of the principal's leadership role and organizational work culture on teacher performance. This study also examines the effect of the relationship between the principal's leadership role and work culture on teacher performance. The type of research used is correlational with data collection tools using questionnaires and the analysis technique used is simple linear regression. The results showed that the F test (35, 772) with a significant level (0.000) <0.05 for the variable leadership role on teacher performance. And the F test (33.043) with a significant level (0.000) <0.05 for the work culture variable on teacher performance. And for the results together the effectiveness of the role of leadership and work culture on teacher performance is the F test (17.757) with a significant level (0.000) <0.05. The results of this study are the role of principals' leadership and organizational work culture in the sufficient category in influencing teacher performance with an R square value of 65%.